500 400-calorie recipes : delicious and satisfying meals that keep you to a balanced 1200-calorie diet so you can lose weight without starving yourself /: delicious and satisfying meals that keep you to a balanced 1200-calorie diet so you can lose weight without starving yourself. (2011) - Unknown
No abstract available